Corporeality in Early Twentieth-Century Latin American Literature - Willis, B. author. aut Link
XI, 234 p.
Keywords: Featuring canonical Spanish American and Brazilian texts of the 1920s and 30s, Corporeality in Early Twentieth-Century Latin American Literature is an innovative analysis of the body as site of inscription for avant-garde objectives such as originality, subjectivity, and subversion.